Implementasi Protokol Routing Directed Diffusion Pada Wireless Sensor Network Menggunakan Media Komunikasi RF - Elsandio Bramudya Putra Fathoni; Sabriansyah Rizqika Akbar; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Implementation of wireless sensor network routing protocols has been carried out specifically on flat topology architectures. Where in the flat topology there are several routing protocols that has been implemented, one of which is directed diffusion routing protocol. Unfortunately, the implementation is done using a network simulation application. Therefore, in this research, the authors implemented routing protocols directed diffusion on a wireless sensor network on a real device that uses RF communication media. Hardwares to build a node using arduino nano 3.0 microcontroller as sensor data processor and NRF24L01 module as data transmission medium. At the time of application of directed diffusion, the sink node send interest or request data containing the coordinates of the sender, the type of data and the coordinates of the destination node. The data used are the temperature and soil moisture data which is selected randomly. The research is done by testing the status of nodes that can be displayed on the serial monitor, each sensor node can perform sensors data and moisture data, as well as testing the directed diffusion as functional requirements. The results of the research is each node successfully displays the node status on the serial monitor, each sensor node can perform sensor data and moisture data, and the system successfully implements the direct diffusion routing protocol.